Fundamental choices in EFO (Advances in Knowledge Representation, 2025)
Abstract. In this article, we continue the study and definition of a class of ontologies known as “epistemic” by laying the foundations for a foundational epistemic ontology called EFO (for Epistemic Foundational Ontology). First, we outline some basic ontological commitments made to establish EFO. We then detail the main categories structuring the ontology. Finally, we sketch out a set of axioms in FOL to formalize a core of EFO.